Reversible Renal Insufficiency Secondary to Extrinsic Splenic Compression of the Kidney in a Patient with Chronic Lymphocytic Leukemia - Miriam Hadj-Moussa; James A. Brown (The Scientific World Journal)
While increased renal venous and direct renal parenchymal pressure may cause renal insufficiency, there are no prior reports of hypersplenism secondary to chronic lymphocytic leukemia (CLL) doing so. This first report of massive splenomegaly leading to marked compression of the left kidney associated with renal insufficiency that resolved after splenectomy illustrates that profound extrinsic renal compression from splenomegaly may significantly compromise left renal function and splenectomy should be considered in this situation.